2016
DOI: 10.1136/bjophthalmol-2016-308869
|View full text |Cite
|
Sign up to set email alerts
|

Vascular abnormalities in patients with Stargardt disease assessed with optical coherence tomography angiography

Abstract: Vascular impairment in patients affected by STGD1 is concentrated in superficial and the deep retinal plexuses. Patients with atrophic changes have a greater reduction in CC density compared with controls ('dark atrophy'). Morphological vascular evaluation may become an important step for predicting STGD1 treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
63
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 20 publications
(10 reference statements)
2
63
0
Order By: Relevance
“…The analysis of the OCT-A images was performed as previously described 7,8 . All of the 3 × 3 mm OCT-A images were collected and exported from the system as a Joint Photographic Experts Group (JPEG) file into the National Institutes of Health ImageJ 1.8.0 (National Institutes of Health, Bethesda, Maryland, USA) image-processing software.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of the OCT-A images was performed as previously described 7,8 . All of the 3 × 3 mm OCT-A images were collected and exported from the system as a Joint Photographic Experts Group (JPEG) file into the National Institutes of Health ImageJ 1.8.0 (National Institutes of Health, Bethesda, Maryland, USA) image-processing software.…”
Section: Methodsmentioning
confidence: 99%
“…The image was converted from 8-bit into red green blue (RGB) color type and was subsequently split into the three channels. We chose the red channel as reference as previously performed 7,8 . The adjust threshold tool was set to default and applied, with the dark-background option selected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The utility of this technique as an alternative to conventional fluorescein and indocyanine green angiography has been explored for numerous retinal and optic nerve diseases in the past few years with encouraging results 5–14. In addition to qualitative features (eg, subjective assessment of foveal ischaemia), several studies have now reported the use of quantitative measures (eg, retinal capillary plexus density measurements) to evaluate severity and prognosis of conditions such as diabetic retinopathy,15 age-related macular degeneration,16 Stargardt disease17 and retinitis pigmentosa 18…”
Section: Introductionmentioning
confidence: 99%
“…OCTA has illustrated retinal and choroidal vascular abnormalities in diseases like retinopathy of prematurity, uveitis, foveal hypoplasia, choroidal tumors, macular telangiectasia, and Stargardt disease 29, 30, 31, 32, 33, 34. These OCTA findings have provided new insights into the pathogenesis of these interesting diseases.…”
mentioning
confidence: 91%